Complications of Radioembolization: Prevention and Management - Gyoung Min Kim (Journal of the Korean Society of Radiology)
Radioembolization is a relatively safe procedure, and most adverse effects are part of the post-embolization syndrome, which includes symptoms such as abdominal pain and fatigue. Although serious complications are rare, when they do occur, they can significantly impact patient outcomes, potentially requiring long-term treatment or even causing death. Therefore, it is essential to thoroughly understand and prevent potential adverse events proactively. This review aimed to classify the complications associated with radioembolization into three categories: 1) complications due to local effects, such as radioembolizationinduced liver disease and biliary injury, 2) complications due to nontarget radioembolization, such as gastrointestinal ulcers and radiation pneumonitis, and 3) complications due to systemic reactions; moreover, we herein describe the causes, symptoms, preventive strategies, and treatments for each type of adverse event.